Penguatan dan Pengamalan Al-Islam dan Kemuhammadiyahan (Ibadah Wajib) pada Tenaga Penunjang UNIMUS: Penelitian - Ali Imron; Danu Purwanto; Suci Izzati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Strengthening Islamic and Muhammadiyah values ​​(AIK) is an important foundation in developing religious attitudes and an Islamic work ethic within the Muhammadiyah Community Service environment. However, support staff such as office boys, drivers, and security guards at the University of Muhammadiyah Semarang (UNIMUS) often do not receive systematic guidance regarding the implementation of obligatory worship, especially the five daily prayers. This community service activity aims to increase understanding, awareness, and consistency in the practice of obligatory worship through an educational, participatory approach and the application of simple learning media. Implementation methods include socialization, andragogy-based worship practice training, the provision of short learning videos, the use of daily worship journals (printed and digital), and routine mentoring. Evaluation was carried out through pre-post tests, observation of worship practices, and participant reflections. The results of the activity showed a significant increase in the understanding and implementation of obligatory worship, reflected in increased post-test scores, regular congregational prayers, and increased spiritual commitment of support staff. In conclusion, this program is effective in strengthening the practice of obligatory worship while building a more harmonious Islamic work culture within the UNIMUS environment.